Profesionalisme Ditinjau Dari Kecerdasan Emosional dan Dukungan Organisasi Kementerian Pekerjaan Umum Direktorat Jendral Sumber Daya Air Wilayah Sungai Sumatera Utara II - AL DA; Bunga Aditi, SE., M.Si; Indra Syafii, SE., MM (CV. Tungga Esti, 2022)
The phenomenon that occurs related to the professionalism of employees at the Directorate General of Water Resources for the North Sumatra II River Basin is employees who are less professional at work. This is evidenced by observations made by researchers by looking at the performance of employees at the Directorate General of Water Resources for the North Sumatra II River Basin. Therefore, this study aims to determine the effect of emotional intelligence and organizational support on professionalism in employees at the Ministry of Public Works, Directorate General of Water Resources, North Sumatra II River Basin. This research was conducted using quantitative methods. The results showed that based on the results of the coefficient of determination, it can be seen that emotional intelligence and organizational support simultaneously (together) contributed or contributed to professionalism of 57.4%. The remaining 42.6% is influenced by other factors outside of emotional intelligence and organizational support.